Based on the synergistic effect of Mg2+ and antibacterial peptides to improve the corrosion resistance, antibacterial ability and osteogenic activity of magnesium-based degradable metals. (19th November 2020) - Zhou, Wenhao; Yan, Jianglong; Li, Yangyang; Wang, Lan; Jing, Lei; Li, Ming; Yu, Sen; Cheng, Yan; Zheng, Yufeng
Abstract : Magnesium (Mg) and its alloys have been widely investigated as the most promising biodegradable metals for orthopedic device applications, but its surface properties should be further improved to overcome the restricted osteogenesis and fast degradation problems. Abstract : To overcome the restricted degradation, poor antiacterial and osteoindctive problems of magnesium and its alloys, this study presented the spinning coating of an antimicrobial peptide (AP)-loaded silk fibroin (SF) composite onto a corrosion-resistant MgO-coated AZ31 Mg alloy via anodization (aMgO) and electrodeposition (eMgO) methods. The composite coatings not only created a smooth and hydrophilic surface, but also obviously improved the corrosion resistance according to the test of corrosion potential and current density. The colonization of E. coli on MgO–AP composite coatings was significantly reduced as compared to the MgO layers, due to the potential synergetic effects of APs and Mg 2+ . Compared with the bare AZ31, the composite coating inhibited the corrosion of the substrate and the release of Mg 2+, supported the adhesion, spreading and proliferation of osteoblasts, and presented a significantly improved osteogenic differentiation trend. Therefore, the MgO–AP composite coating, which had both antibacterial and bone-promoting abilities, was expected to be applied for surface modification of magnesium alloy implants to solve the clinical problems of bacterial infection and poor osseointegration.